تحضيرات بناء الأسرة في بلاد المغرب والأندلس ما بين القرنين(5-6ه/11-12م) من خلال النوازل الفقهية - هيصام دلال; هواري موسى (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى محاولة إلقاء الضوء على تحضيرات بناء الأسرة في كل من بلاد المغرب والأندلس ما بين القرنين (5-6ه/11-12م) من خلال كتب النوازل الفقهية، باعتبارها مرآة عاكسة للواقع المعاش في المجتمع المغربي والأندلسي على حد سواء، والذي اتضح من خلالها أن تحضيرات بناء الأسرة عادة ما كانت تبدأ بالخِطبة التي تعتبر من أهم مراحل بناء الأسرة، إذ تعد أول خطوة لحصول الرضا والقبول بين الزوجين، وتكوين صورة واضحة لهما، والملاحظ أيضا أن الخِطبة عادة ما كانت تخضع لمجموعة من المعايير التي تحكمت في عملية اختيار الزوج لزوجته، والتي إما حددت بقاعدة شرعية، أو ارتبطت بالعادات والتقاليد السائدة في بلاد المغرب والأندلس آنذاك، ومن النتائج المتوصل إليها من خلال هذه الدراسة أيضا أن المرأة كانت تُستأذن في أمر زواجها في غالب الأحيان، على الرغم من أن الأعراف السائدة حينها كانت قائمة على أن يتولى الولي أمر تزويج ابنته دون الحاجة إلى أخذ رأيها، وذلك باعتباره الناظر لها، والعارف بمصلحتها. This study aims to attempt to shed light on the family construction preparations in the Maghreb and Andalusia between the two centuries (5- 6 Hijri/11-12 Ad) through the books of controversial issues in Fiqh as a mirror reflective of the living reality in the Maghreban and the Andalusian society, from which it became apparent that the family’s construction usually used to start with the sermon which is one of the most important stages of family construction. It is the first step to acquire satisfaction and consent between spouses and make a clear picture of them. It is also noted that the sermon was usually subject to a set of criteria that governed the process of the husband's choice of his wife, which either were identified by a legal rule, or were associated with customs and traditions prevailing in the Maghreb and Andalusia at the time.One of the conclusions reached through this study is that, although the prevailing customs at the time were that the father would marry his daughter without having to take her opinion, as being her supervisor and who knows her Best interest, the woman often was asked about her marriage.
Keywords: الخِطبة; لأسرة; الزواج; لأندلس; بلاد المغرب; النوازل; المرأة; Sermon; Family; Marriage; Al-Andalus; Al-Maghrb; Woman